Zarpo Desvairado: A transgressão espaço- temporal em Macunaíma - Neves, Siméia de Castro Ferreira (2016)
The present paper has as object of study the work of Mario de Andrade “Macunaíma”, in which we investigate the displacements of spacial transgression performed by the protagonist. In the above-mentioned novel, we noticed that the tapanhuma hero wanders through several places of national and international territories trying to recover his sacred amulet, dear remembrance of his beloved Ci, the mother of woods. However, among the spaces that make up the story, we realized that such character does not accomplish a linear displacement. With that said, we aim with this analysis: find the highest level in the studied category, understand its context, besides knowing which moments of spacial violation are explicit and what are the motives for such occurrences. Therefore, we resorted to the physical and literary conceptions about space in the laws of Borges Filho (2008). For the presentation of space in the above-mentioned work we used the studies of Proença (1978), followed by a map of the displacements in which the main character breaks the principles of modern physics. In order to analyse the clímax of space transgression, we used as foundation the studies of Benjamin (1985), Lopez (1988), Candido (2008) and Teles (2009), proposing three main motives for this constant violation, such as: the persecutions suffered by the protagonist, the interference of the narrative voice and/orr the modernist esthetical proposal.